Smart Safety Helmet for Safe Coal Mining - Beenish Fayyaz (JISR on Computing, 2021)
In any production and service industry, the safety of their workers/labors is very critical. The workers directly related with production are generally more prone to the threats because of their exposure to electro-mechanical, chemical, thermal, environmental, civil and other hazards. The coal mining industry in one of the most risky industries in terms of workers’ lives hazards. In the under-developed countries, any potential disaster in the underground mining turns into huge catastrophic losses of both the human lives and equipment. This paper presents some statistical data of mining disasters worldwide and propose an architecture for a smart helmet to be used by miners for their safe working inside the coalmines.